2005
DOI: 10.1111/j.1365-2745.2005.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Successional dynamics of woody seedling communities in wet tropical secondary forests

Abstract: Summary1 Chronosequence studies have found that shrubs and lianas are generally more abundant in early stages of tropical forest succession, whereas canopy trees and palms become more abundant and species-rich in older stages and mature forests. 2 We analysed changes in woody seedling communities over 5 years in four secondgrowth forests (initially 13-26 years after pasture abandonment) in Costa Rica. We recorded community-level changes in woody seedling density, species density, species richness and compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 36 publications
10
78
0
8
Order By: Relevance
“…This could be because the younger plot was still in the preliminary phase of colonisation whereby newer species are still arriving, whereas the older plots have attained some level of stability and tending towards another successional phase. This supports the assertion of Capers et al (2005) who reported that evenness of species appear to increase for at least 30 years after pasture abandonment in wet tropical forests in Costa Rica. They attributed this to an increase in tree species as a proportion of all species with successional age and also because the proportion of rare tree species was higher in the oldest site than in the youngest.…”
Section: Discussionsupporting
confidence: 80%
“…This could be because the younger plot was still in the preliminary phase of colonisation whereby newer species are still arriving, whereas the older plots have attained some level of stability and tending towards another successional phase. This supports the assertion of Capers et al (2005) who reported that evenness of species appear to increase for at least 30 years after pasture abandonment in wet tropical forests in Costa Rica. They attributed this to an increase in tree species as a proportion of all species with successional age and also because the proportion of rare tree species was higher in the oldest site than in the youngest.…”
Section: Discussionsupporting
confidence: 80%
“…Areas undergoing secondary succession in general become more diverse with time, but species composition is slow to recover or converge between sites, even those that are close together (Capers et al 2005). In our study, diversity and the number of current year recruits decreased over the dry season; for diversity, this pattern was more pronounced in burned plots.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments largely or entirely consisting of edge-affected habitats cannot retain a full complement of life-history traits in plant communities, and consequently the plant-animal interaction webs constitute distorted communities. Therefore, the conservation value of small forest fragments will largely depend on the mitigation of edge effects (and their cascades of species extirpation) via a combination of landscape-scale landuse regulations, e.g., keeping landscape structural connectivity via protection of gallery forest [8], plus fragment-scale assisted interventions such the control of liana populations [46], species reintroduction and enrichment [47][48], assisted seedling recruitment [49], and fragment buffering via second-growth vegetation [48,50]. Such interventions may be rendered ineffective by a priori assumptions that aging fragments immersed in open-habitat matrices are concentric-shaped in terms of microclimatic/biological configuration.…”
Section: Discussionmentioning
confidence: 99%